2022
DOI: 10.18805/ag.r-2404
|View full text |Cite
|
Sign up to set email alerts
|

​Influence of Micro Climatic Indices on Growth and Yield of Direct Seeded Upland Rice (Oryza sativa L.) Varieties in Assam

Abstract: Background: Rice (Oryza sativa L.) is the major cereal crop grown in India. Rice plays a pivotal role in the socio-cultural life of the people of Assam. The main objective of this study to investigate the influence micro climatic indices in relation to crop growth and yield of upland rice varieties with different dates of sowing in Assam. Methods: A field experiment was carried out at Instructional cum Research Farm, Assam Agricultural University, Jorhat during autumn season of 2017. The experiment consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Growth attributes such as plant height and tiller number hill-¹ were found to be higher under sprinkler irrigation at 125% Epan" [38]. Anusha et al [39] reported that drip irrigation at 2.0 Epan throughout growth stages recorded higher productive tillers (no hill -1…”
Section: Micro Irrigation Methodsmentioning
confidence: 99%
“…Growth attributes such as plant height and tiller number hill-¹ were found to be higher under sprinkler irrigation at 125% Epan" [38]. Anusha et al [39] reported that drip irrigation at 2.0 Epan throughout growth stages recorded higher productive tillers (no hill -1…”
Section: Micro Irrigation Methodsmentioning
confidence: 99%